The French ideology - Lepeshko, Boris M. (Journal of the Belarusian State University. Sociology, 2019)
The article deals with the ideological peculiarities of the events of may 1968 in France. Definitions are critically comprehended, broad analogies with other important processes of the XX – beginning of the XXI century. The ideological platform of the student movement is considered, peculiarities of its national context are pointed out. The role of power structures and the President of the country in the middle of 1968 is investigated. The possibility of determining the nature and character of the processes under consideration from the point of view of integrative methodology is characterized.